REPRESENTATION OF THE NATIONAL CULTURAL CONCEPT IN OCCASIONALISMS (SCIENCE TIME JOURNAL, 2026)
Occasionalisms are creative, context-bound lexical units that emerge in specific communicative situations and often exist outside standard dictionaries. Despite their temporary nature, they carry strong expressive and cultural meanings. This article explores how national cultural concepts are reflected through occasionalisms from a cognitive and linguocultural perspective. The analysis shows that occasional word formations are not random innovations but culturally motivated linguistic signs that reflect collective worldview, emotional perception, and national identity. The findings highlight the close relationship between language creativity and cultural conceptualization.